2021
DOI: 10.3390/su13094872
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Electric Vehicles and Hydrogen Fuel Cell Vehicles Using the GREET Model—A Comparative Study

Abstract: Facing global warming and recent bans on the use of diesel in vehicles, there is a growing need to develop vehicles powered by renewable energy sources to mitigate greenhouse gas and pollutant emissions. Among the various forms of non-fossil energy for vehicles, hydrogen fuel is emerging as a promising way to combat global warming. To date, most studies on vehicle carbon emissions have focused on diesel and electric vehicles (EVs). Emission assessment methodologies are usually developed for fast-moving consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…The technical documents of the balancing vehicle were provided to support students in defining the goal and scope, including performance parameters, manufacturing processes, three-dimensional models, and bills of materials. The consumption and pollution algorithms help participants perform inventory analysis and environmental impact assessment, such as the GREET model [31]. The normalization algorithm is given to achieve the equivalence between different measurement units, such as 1MMBtu = 293 kW•h.…”
Section: ) Phase_2: Lca Practicementioning
confidence: 99%
“…The technical documents of the balancing vehicle were provided to support students in defining the goal and scope, including performance parameters, manufacturing processes, three-dimensional models, and bills of materials. The consumption and pollution algorithms help participants perform inventory analysis and environmental impact assessment, such as the GREET model [31]. The normalization algorithm is given to achieve the equivalence between different measurement units, such as 1MMBtu = 293 kW•h.…”
Section: ) Phase_2: Lca Practicementioning
confidence: 99%
“…The range of objects that have been studied in previous LCA studies has varied from food products to buildings to motor vehicles (De Benedetto and Klemeš 2009). The LCA methodology in several previous contributions regarding vehicles differentiated the production and use phases (Puig-Samper Naranjo et al 2021;Wong et al 2021). The rst stage involves calculating the total emissions of the fuels used from production to use, while the second stage calculates the total emissions of the vehicles considered, from the extraction of the various raw materials (mostly metals) used in their production to the end of the average life of the vehicle (Pero et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they also reported that the environmental performance of electric scooters in Germany is highly dependent on the share of different energy sources in the German electricity mix. Wong et al 15 compared the LCA of electric vehicles (Tesla Model 3) and hydrogen fuel cell vehicles (Toyota MIRAI) and employed LCA by using the processes of GREET (greenhouse gases, regulated emissions, and energy use in transportation). They reported that fuel cell vehicles contribute significantly to the product carbon footprints of both vehicles followed by a cleaner production of hydrogen results lower negativity on the environment.…”
Section: Introductionmentioning
confidence: 99%